Protracted Bacterial Bronchitis, it is a Myth? - Fadzil, Ahmad (IIUM Medical Journal Malaysia, 2021)
Protracted wet and productive chronic cough is a symptom that indicate there is an underlying cause and the possibility vary from a simple to serious medical conditions. If the cough is accompanied with specific pointers in signs and symptoms, the diagnosis is apparent. Nevertheless, the challenge is to identify the diagnosis in children who cough without specific pointers. Recently, protracted bacterial bronchitis is one of the conditions that was proposed and postulated to conceive this clinical presentation. Since then, the understanding of PBB has escalated and deepened. However, there is still no unanimous consensus in definition, pathophysiology, diagnostic, treatment, long term outcome and even the entity itself. Further research is required to refine understanding of this condition in several facets therefore patients can be treated accordingly.